2010
DOI: 10.1177/0734242x10371355
|View full text |Cite
|
Sign up to set email alerts
|

Electricity and combined heat and power from municipal solid waste; theoretically optimal investment decision time and emissions trading implications

Abstract: This version is available at https://strathprints.strath.ac.uk/44930/ Strathprints is designed to allow users to access the research output of the University of Strathclyde. Unless otherwise explicitly stated on the manuscript, Copyright © and Moral Rights for the papers on this site are retained by the individual authors and/or other copyright owners. Please check the manuscript for details of any other licences that may have been applied. You may not engage in further distribution of the material for any pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…Apart from the challenge in power provision, a significant increase in the amount of waste has become a common global environmental problem. Thus, a proper strategy for waste management is imperative as it is a vital part for sustainability and environmental protection [10]. An appropriate approach should minimize the amount of waste and maximize its recovery for profitable utilization [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from the challenge in power provision, a significant increase in the amount of waste has become a common global environmental problem. Thus, a proper strategy for waste management is imperative as it is a vital part for sustainability and environmental protection [10]. An appropriate approach should minimize the amount of waste and maximize its recovery for profitable utilization [11].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, due to its relative newness compared to older and proven technological options, its risk can delay private investment. For private sector to invest in this field, economic profit should be assured [10]. It has been identified that the high cost of implementation is the most important barrier in environmental management systems [15].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the need for a proper waste management strategy is inevitable as it is a vital part of sustainability and environmental protection [1]. An appropriate approach should minimize the amount OPEN ACCESS of sewage sludge and maximize its recovery to useful utilization [2].…”
Section: Introductionmentioning
confidence: 99%
“…According to the studies of specialists [38][39][40][41][42][43][44][45], several thermochemical incineration technologies have been identified: (1) the principle of the process involving the complete oxidation of waste; (2) the type of exothermic reaction; (3) requirements for raw materials taking into account dry waste of biological and synthetic origin; (4) the method of pre-processing the raw material by drying and pelletizing; (5) the permitted moisture content of the raw material of 25-30%; (6) temperature (700-14,000 • C); (7) endurance time (minutes/seconds); (8) final products (heat and ash); (9) environmental issues (ash leakage and toxic gases); (10) cost of capital (medium-high); (11) degree of efficiency (50-60%); (12) product applications (heat and power applications, aggregate and filler); and ( 13) future (moderate) potential. The advantages of thermochemical incineration technology include: (1) the resulting ash can be used as a low-cost aggregate or filler for construction works on bridges, roads and highways; (2) it has relatively low capital requirements, requires less skilled labor compared to other WTE technologies and is more suitable for rural and urban areas; (3) it significantly reduces waste storage space; and (4) it has high energy generation efficiency and low emission rates due to the installation of pollution content control devices in incinerators that help maintain the emission limits required by law [44,[46][47][48][49][50][51].…”
Section: Incinerationmentioning
confidence: 99%